Dampak Diplomasi Bisbol Amerika Serikat di Kuba Pada Tahun 2014-2016 - Anabela Maria Lucia Sinambela; Rio Ferdian Firmansyah; Sharla Putri Aisha; Ario Bimo Utomo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The relationship between Cuba and the United States initially developed during the colonial period following the Spanish-American War and lasted until 1902. At that time, Cuba was a colony of the United States and formally declared its independence in 1901 after a congress held in the United States. However, following Cuba’s independence, bilateral relations gradually deteriorated, particularly after the 1959 revolution led by Fidel Castro, which transformed Cuba into a communist state. This development raised significant concerns in the United States, particularly regarding Cuba's increasing alignment with the Soviet Union during the height of the Cold War. In response to these geopolitical tensions, the United States sought various strategies to improve its international image, including within the Middle East. One such approach involved the use of sports diplomacy, specifically through baseball, as a means of fostering engagement with Cuba and improving its global reputation. This study aims to examine the impact experienced by Cuba as a result of the baseball diplomacy initiatives conducted by the United States between 2014 and 2016.